Regional success after Brexit : the need for new measures - Hearne, David; de Ruyter, Alex (Brexit studies series, 2019)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatchedfunding,and freely available to read online. The post-Brexit environment introduces notable challenges for regional policy; however, it also offers the opportunity to reassess regional needs and appropriate funding formulae.Regional Success After Brexit: The Need for New Measures examines the metrics currently used to evaluate regional performance within the UK and, in the wake of Brexit, suggests better alternatives. Alongside an in-depth critique of GVA/capita, the book challenges current thinking based on nominal productivity differences and advocates measures based on real incomes, real living standards and real labour productivity. The book is an illuminating read for academics, researchers and policy-makers working within regional economics as it exposes the need to replace European regional funding with a new formula that takes regional prices into account and redistributes authority over the UK's revenue and spending to the regions.